Search for new physics in dijet mass and angular distributions in pp collisions at √s=7 TeV measured with the ATLAS detector - Dietzsch, Thorsten (Pramāna, 2012)
We present a search for physics beyond the Standard Model in proton-proton collisions at a centre-of-mass energy of s√=7TeVs=7TeV\sqrt{s} = {7}\;{\rm{TeV}}, performed with the ATLAS detector at the Large Hadron Collider (LHC). No evidence for new physics is found in dijet mass and angular distributions and stringent limits are set on a variety of models of new physics, including excited quarks, quark contact interactions, axigluons, and quantum black holes.